ChemInform Abstract: Selective Hydrogen Peroxide Oxidation of Sulfides to Sulfoxides or Sulfones with MWW‐Type Titanosilicate Zeolite Catalyst under Organic Solvent‐Free Conditions. Issue 10 (March 2015) - Kon, Yoshihiro; Yokoi, Toshiyuki; Yoshioka, Masato; Tanaka, Shinji; Uesaka, Yumiko; Mochizuki, Takehisa; Sato, Kazuhiko; Tatsumi, Takashi
Abstract An MWW‐type titanosilicate zeolite catalyst with interlayer‐expanded structure exhibits the highest activity combined with good chemoselectivity.